The Effectiveness of Sweet Orange Certificate in Recovering Media of Salt Duck Eggs on Fat Levels and Sensoric Quality - I. Irmawaty; A. Astati; Muhammad Nur Hidayat; Jumriah Syam; Nur Azmi; Muhammad Arsan Jamili (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
Salted eggs are livestock products that have undergone a salting process to extend shelf life, add flavor, and increase consumer tastes. The fat content in duck eggs is very high, reaching 35-34%, concentrated in egg yolks. It could be dangerous if consumed in excess; therefore, a study was conducted to determine the fat content of salted duck eggs with the addition of sweet orange juice (Citrus). sinesis L). This study used sweet orange juice (Citrus sinesis L) with different concentrations of 0% (control), 80% (P1), 90% (P2), 100% (P3), and 100% commercial Vitamin C. (Vicee) (P4). The research used a completely randomized design (CRD) consisting of 5 treatments and four replications. Each replication consisted of 2 eggs. Parameters observed were sensory quality (yolk color, Aroma, Taste, grit) and fat content of salted duck eggs. The results showed that the addition of sweet orange juice (Citrus sinesis L) on sensory quality (yolk color, aroma, taste, grit) had no significant effect (P0.05). Meanwhile, the fat content in egg yolk had a significant effect (P0.05).